2018
DOI: 10.1038/s41467-018-04074-2
|View full text |Cite|
|
Sign up to set email alerts
|

High frequency temperature variability reduces the risk of coral bleaching

Abstract: Coral bleaching is the detrimental expulsion of algal symbionts from their cnidarian hosts, and predominantly occurs when corals are exposed to thermal stress. The incidence and severity of bleaching is often spatially heterogeneous within reef-scales (<1 km), and is therefore not predictable using conventional remote sensing products. Here, we systematically assess the relationship between in situ measurements of 20 environmental variables, along with seven remotely sensed SST thermal stress metrics, and 81 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
302
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(327 citation statements)
references
References 75 publications
22
302
3
Order By: Relevance
“…Coral cover on the Heron reef flat has historically ranged between 0 and 20%, which is consistent with our observations of coral cover (∼18%) (Connell et al, 2004). Although hard corals are believed to be sensitive to environmental extremes, recent studies have shown that corals are able to persist in marginal conditions of lagoon habitats (Camp et al, 2017) and increased temperature variability reduces the likelihood of coral bleaching (Safaie et al, 2018). Instead, persistently low coral cover in the Heron lagoon appears to be due to reduced coral recruitment due to the lack of hard substrate (Connell et al, 2004).…”
Section: Modeling the Effect Of Benthic Cover On The Frequency Of Corsupporting
confidence: 89%
“…Coral cover on the Heron reef flat has historically ranged between 0 and 20%, which is consistent with our observations of coral cover (∼18%) (Connell et al, 2004). Although hard corals are believed to be sensitive to environmental extremes, recent studies have shown that corals are able to persist in marginal conditions of lagoon habitats (Camp et al, 2017) and increased temperature variability reduces the likelihood of coral bleaching (Safaie et al, 2018). Instead, persistently low coral cover in the Heron lagoon appears to be due to reduced coral recruitment due to the lack of hard substrate (Connell et al, 2004).…”
Section: Modeling the Effect Of Benthic Cover On The Frequency Of Corsupporting
confidence: 89%
“…Therefore, we expected the large inputs of nitrogen and phosphorous from seabird guano to enhance resis- Instead of depending on proximity to seabird colonies, the response of corals to bleaching varied by atoll. One likely explanation for this pattern is that corals from small lagoons are adapted to warmer water and/or greater temperature variability and thus are better able to withstand temperature stress (Donner, 2011;Guest et al, 2012;Middlebrook, Hoegh-Guldberg, & Leggat, 2008;Oliver & Palumbi, 2011;Safaie et al, 2018;Schoepf, Stat, Falter, & McCulloch, 2015). Other field studies have similarly demonstrated reduced susceptibility to bleaching for corals in sheltered areas with low water flow (Hoogenboom et al, 2017;McClanahan, Ateweberhan, Muhando, Maina, & Mohammed, 2007;Pineda et al, 2013;Sheppard, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…The difference between the DHW with and without internal waves (ΔDHW) is 0.7°C‐weeks. A synthesis study of factors influencing coral bleaching (Safaie et al ) predicts that an increase in cumulative thermal anomaly, ΔDHW = 0.7°C‐weeks would result in approximately four times the probability of a more severe bleaching event on this reef without the influence of internal waves.…”
Section: Discussionmentioning
confidence: 99%
“…However, variation in the physiological responses of individual coral colonies and reefs to environmental stresses suggests critical differences in corals’ resilience and/or environmental conditions over small spatial and temporal scales (Riegl and Piller ; Pandolfi et al ; van Woesik et al ; van Woesik et al ). For example, water temperatures and thermal tolerance can vary substantially across an individual reef (e.g., Pineda et al ; Palumbi et al ; Safaie et al ) and some coral communities thrive in naturally acidified waters (Shamberger et al ; Barkley et al ). Thus, coral organisms with greater resilience and adaptive capacity may persist under future climate change (Pandolfi et al ; Spalding and Brown ).…”
mentioning
confidence: 99%
See 1 more Smart Citation